Implementation And Effect Of Sensor Technology In Building Level Balancer Using Programmable Integrated Circuit Microcontroller - Mohamad, Najmiah Radiah; Ab Ghani, Mohd Sabri; Salleh, Azahari; Hashim, Nik Mohd Zarifie; Ab Hadi, Nik Azran (International Journal for Advance Research in Engineering and Technology, 2015)
-